+0  
 
0
163
3
avatar

a = (2b^7*²)+5c - (6bc²) =

 18.11.2018
 #1
avatar+8227 
0

a = (2b^7*²)+5c - (6bc²) =

 

Hallo Gast!

 

Ist dein Term so gemeint  \(a=2b^{7*2}+5c-6bc^2\) ?

oder so     \(a=2b^{7^2}+5c-6bc^2\)   ?

und was soll damit geschehen ?

laugh  !

 18.11.2018
 #2
avatar
0

Das erste

Gast 18.11.2018
 #3
avatar+8227 
0

Hallo Gast!

 

\(\color{BrickRed}a=2b^{7*2}+5c-6bc^2\\ a-5c=2b^{14}-6bc^2\\ a-5c=2b(b^{13}-3c^2)\)

 

Mehr geht nicht.

laugh  !

 18.11.2018

34 Benutzer online

avatar
avatar